Consumer health informatics: new services, roles, and responsibilities - Wetter, Thomas (Springer, 2015)
Intro -- Foreword -- References -- Preface -- Contents -- Part I Introducing the Domain and Levels of Service -- 1 Character of Domain and Organization of Book -- 1.1 Introduction -- 1.1.1 Pioneers -- 1.1.1.1 Baby CareLink -- 1.1.1.2 IDEATel -- 1.1.1.3 PCASSO -- 1.1.2 An Inspiration -- 1.2 Consumer Health Informatics as a Discipline -- 1.2.1 What Defines Consumer Health Informatics? Helpful Terms -- 1.2.1.1 Definition -- 1.2.1.2 Client, Subject, User: New Names for New Patient Roles -- 1.2.1.3 Telemedicine Patients Versus Consumer Health Informatics Clients -- 1.2.2 Consumer Health Informatics asa Scientific Discipline -- 1.2.3 Consumer Health Informatics as Rangeof Phenomena -- 1.2.3.1 Searching and Finding: Transient Encounters -- 1.2.3.2 Awareness, Assessment and Screening -- 1.2.3.3 Technology Enhanced Treatment: Adding Channels of Communication -- 1.2.3.4 Lifelong Resource: Fostering Client Ownership -- 1.2.3.5 Lifelong Attitude: Fostering Client Commitment -- 1.2.3.6 Sensor Rich Surveillance: Using the Physical Environment -- 1.2.3.7 Leveraging Client Wisdom: Using the Knowledge Environment -- 1.3 Core Methodology -- 1.3.1 Search Support -- 1.3.2 Data Sharing -- 1.3.3 Interface Design -- 1.3.3.1 General Usability Heuristics -- 1.3.3.2 Balancing Appeal, Change, and Core Content -- 1.3.3.3 The Added Value of Multimedia -- 1.3.4 User Assessment and Personalization -- 1.3.4.1 Literacy -- 1.3.4.2 Client Personal Background -- 1.3.4.3 Personalization -- 1.3.5 End User Participation -- 1.4 Supportive Methodology -- 1.4.1 Evaluation -- 1.4.1.1 Trials -- 1.4.1.2 Client Safety Assessment -- 1.4.1.3 Cost Effectiveness Analysis -- 1.4.1.4 Non-inferiority -- 1.4.2 Going Life -- 1.4.2.1 Legal and Ethical Analysis -- 1.4.2.2 Sustained Funding -- 1.5 Hardware -- 1.5.1 Voice and Sound -- 1.5.2 Biosignals -- 1.5.3 Pointing and Virtual Space.
Includes bibliographical references and index